Briket Ramah Lingkungan Berbasis Limbah Organik: Integrasi Kertas Bekas Sebagai Perekat pada Limbah Pertanian - Legawati, Lisa; Roza, Roza; Ermal, Dini Aulia Sari; Maarasyid, Cici; Israyandi, Israyandi; Fithry, Dwi Annisa (SURYA TEKNIKA, 2025)
One of the solid wastes from oil palm is the frond, which can be utilized to produce briquettes an alternative fuel. This study investigates the utilization of oil palm frond waste and sugarcane bagasse for briquette production, using different binders like tapioca flour and pulp at concentrations of 3%, 5%, and 8%. The research methodology involved comparing the moisture content, ash content, and calorific value of each treatment applied. The results showed that briquettes with 3% tapioka flour binder produced the best quality, with a moisture content of 3.6%, ash content of 4.4%, and a calorific value above 6,000 cal/g, meeting the quality standards of SNI 01-6235-2000. The implications of these findings indicate the potential of biomass briquettes as an environmentally friendly alternative energy source. However, this study was limited to laboratory testing without application trials or economic analysis. Further research is recommended to evaluate production scale and economic feasibility.